PERAN KELEMBAGAAN NON STRUKTURAL DALAM PRAKTIK DESENTRALISASI : STUDI KASUS PADA BPK2L, BPPB SIMA DAN DP2K KOTA SEMARANG - Saputra, Dimas Adi; ., Kushandajani (Journal of Politic and Government Studies, 2018)
There is an absence of a theory explaining the non-structural institutional practice of autonomous regions in Indonesia, which is part of new public management form of decentralization. This has an effect on the increasingly unfamiliar role of civil society combined agencies and governmental elements in order to assist in the delivery of public services. Yet this relatively new institutional model, able to address the issue of substantial democracy in developing countries such as Indonesia, which affects the quality of development of a region. At the praxis level, the increasing variety of challenges both domestically and internationally and the demands of fast-paced and instant society make the central government institutions overwhelmed to answer the various policy issues. What is the role of nonstructural institutions in order to participate in local governance?This research analyzes the role of 3 non-structural institutional in Semarang City such as Semarang City Bureau Management Board, Sima Polder Management Board and Town Planning Development Board of Semarang in local governance through interview, literature study and a series of observations on activities in the three of non-structural institutions during November 2016 until November 2017.The results show that the role of non-structural institutions involving various stakeholders, both civil society elements and government elements, is able to accelerate the process of public participation in the framework of urban development, to present informal communication in the context of the effectiveness of public policy socialization, policy issues that are easily identified and able to present experts who comes from diverse educational backgrounds and experiences to take an active role in providing policy solutions and alternatives. Keyword : Functional decentralization, Substantial Democracy and Non Structural Organization